Inclusion Practices and Emergency Remote Teaching from the Perspective of Classroom Teachers - Emrah Bilgiç (Sakarya University, 2023)
The recent Kahramanmaraş earthquake and the COVID-19 pandemic led to the implementation of emergency remote teaching (ERT) to prevent the interruption of education services. This rapid implementation of ERT in the educational process led to many new experiences for classroom teachers in implementing teaching activities for students with special educational needs (SWD) in terms of successful inclusion practices (SIP). It is essential to have information about the teachers' experiences of SIP through ERT to determine which strategies they used to cope with the difficulties experienced in this process, to assess their needs and suggestions about the process, and to take measures to overcome these difficulties to realize effective teaching in case similar disasters occur again in the future. This study aims to determine the experiences of classroom teachers on ERT practices for effective instruction for SWD in the process of SIP. The study adopts qualitative research, and a phenomenological design was utilized to analyze classroom teachers' experiences on the subject in depth. The participants of the study consisted of eight primary school classroom teachers. The research data were obtained using a semi-structured interview form applied to the participants. Through thematic analysis of the qualitative data obtained, themes, sub-themes, and codes were created and analyzed. The findings showed that the ERT process carried out within the scope of SIP has advantages and disadvantages for teachers and SWD. The Advantages and disadvantages of teaching basic academic skills (Turkish, mathematics, life science, social studies, and science) were also identified. In addition, it was concluded that teachers have needs and expectations in the SIP process for SWD, and if necessary, studies are carried out in this regard; the more comprehensive distance education method can be used in the relevant process instead of the ERT method. Research findings were discussed within the literature framework, and limitations and recommendations were stated.